2012
DOI: 10.1016/j.bbi.2012.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Maternal immune activation yields offspring displaying mouse versions of the three core symptoms of autism

Abstract: The core symptoms of autism are deficits in social interaction and language, and the presence of repetitive/stereotyped behaviors. We demonstrate that behaviors related to these symptoms are present in a mouse model of an environmental risk factor for autism, maternal infection. We stimulate the maternal immune system by injecting the viral mimic poly(I:C) during pregnancy, and analyze the social and communicative behaviors of the offspring. In one test, young pups respond to a brief separation from the mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
464
8
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 582 publications
(535 citation statements)
references
References 64 publications
40
464
8
2
Order By: Relevance
“…To investigate repetitive/stereotyped behaviors,19 we observed jumping and self‐grooming behaviors of tested mice in a clean, empty box for 10 min. The box was made of white plastic (40 × 40 × 40 cm).…”
Section: Methodsmentioning
confidence: 99%
“…To investigate repetitive/stereotyped behaviors,19 we observed jumping and self‐grooming behaviors of tested mice in a clean, empty box for 10 min. The box was made of white plastic (40 × 40 × 40 cm).…”
Section: Methodsmentioning
confidence: 99%
“…Maternal effects on fetal development have been explored in other mouse models related to autism, but these studies have focused on environmental stressors that impact the prenatal environment (Bronson and Bale, 2014;Malkova et al, 2012). Recent studies related to mood and anxiety have indicated that genetic factors may also influence neurodevelopment by altering maternal physiology during pregnancy (Toth, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The authors followed-up by challenging pregnant dams with either a single injected dose of influenza on embryonic day E9.5 or poly(I:C) on day E12.5; both groups had offspring with altered cerebellar development, akin to that seen in autism (Shi et al, 2009). A more expansive study injected pregnant mice three times with poly(I:C), each with one-fourth the dose of Shi, et al, starting on E10.5 and spaced with 2 days between injections (Malkova et al, 2012). The authors looked at ultrasonic vocalization (USV) responses among male offspring and found lower rates and total length of vocalizations.…”
Section: Maternal Immune Activationmentioning
confidence: 99%